Plasmacytoma of the Sternum with Amyloid Deposition – A Cytological Diagnosis - Durre Aden; Prajwala Gupta; Purnima Paliwal; Minakshi Bhardwaj (Archives of Medicine and Health Sciences)
Plasmacytoma with amyloid deposition to be diagnosed on cytology is rare. In the absence of typical clinical presentation and radiological findings, the diagnosis of plasmacytoma may not be suspected. Fine-needle aspiration cytology (FNAC) in these patients may help in early and definitive diagnosis, thus helping inappropriate management of such patients. We report a case of plasmacytoma of the sternum with amyloid deposition who presented with suprasternal swelling. Apart from being a rare and interesting finding, this case highlights the usefulness of FNAC in making an early diagnosis of patients having an atypical presentation.